2013
DOI: 10.1007/s11096-013-9836-2
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing difficulties with oral drugs among polypharmacy patients attending community pharmacies

Abstract: We report a fairly high prevalence of swallowing difficulties in polypharmacy patients attending their community pharmacies. Pharmacists have to interview patients on their swallowing difficulties in a more systematic way, support patients in finding solutions and refer them to their physician if necessary to ensure continuity in care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
124
4
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(142 citation statements)
references
References 12 publications
3
124
4
4
Order By: Relevance
“…Incidences of medication related swallowing difficulties might have contributed to these findings, as this a wellknown problem across all ages. A small number of studies investigating this issue in the general adult 205 population have reported prevalence rates between 9% to 40% (Marquis et al, 2013, DeRoche et al, 2003, Schiele et al, 2013. Remarkably, these studies have indicated a gender effect, with a significantly higher frequency of difficulties among females compared to males.…”
Section: Tablets and Capsulesmentioning
confidence: 99%
“…Incidences of medication related swallowing difficulties might have contributed to these findings, as this a wellknown problem across all ages. A small number of studies investigating this issue in the general adult 205 population have reported prevalence rates between 9% to 40% (Marquis et al, 2013, DeRoche et al, 2003, Schiele et al, 2013. Remarkably, these studies have indicated a gender effect, with a significantly higher frequency of difficulties among females compared to males.…”
Section: Tablets and Capsulesmentioning
confidence: 99%
“…7,8 There are a number of safety and efficacy concerns around modified medicines such as reduced dose accuracy, reduced drug stability and the potential to affect the pharmacokinetic and pharmacodynamic profile of the drug in vivo. [9][10][11][12][13][14] Guidelines advise that modifications should only be undertaken as a "last resort" 15 when "other methods have been considered".…”
Section: Introductionmentioning
confidence: 99%
“…This value is higher than the Australian population demographic of community pharmacy customers in the same city (16.5%) (Lau et al, 2015) or patients taking three or more different solid oral dose forms (22.5%) (Marquis et al, 2013). However it is similar to the 26% of the general population reported in Norwegian population (Andersen et al, 1995, Chisaka et al, 2006, Wright, 2002, Kottke et al, 1990) and 32% of adolescents in Denmark (Hansen et al, 2008).…”
Section: Discussionmentioning
confidence: 51%
“…New Zealand (Tordoff et al, 2010) 75-85 316 Community-dwelling 14% Germany (Schiele et al, 2013) 18-80 1051 General practice 37.4% Switzerland (Marquis et al, 2013) 19-96 410 Community pharmacy customers 9% ongoing, 13.4% past Australia (Mercovich et al, 2014) NA 160 Aged care facilities (two) 18% UK (Liu et al, 2016) 65+ 156 Community pharmacy customers 7.8% Australia (Lau et al, 2015) 25-60 369 Community pharmacy customers 16.5%…”
Section: +mentioning
confidence: 99%